Colorectal cancer screenings: a single center experience - Viani, Lorenzo; Dell'Abate, Paolo; Del Rio, Paolo; Marchesi, Federico; Tartamella, Francesco; Rossini, Matteo; Bertocchi, Elisa; Giuffrida, Mario (Acta Biomedica Atenei Parmensis, 2020)
Aim: evaluating the impact of screening programmes on colorectal cancer (CRC) in Italy. Methods: we studied 1292 patients with colorectal cancer. Data were collected from January 2004 through December 2015 in Parma University Hospital. We compared clinophatological features to evaluate the real impact of screening programmes on detecting early stage colorectal cancers in target population. Results: screening programmes with fecal occult blood test (FOBT) and colonoscopy covered only patients from 50 to 69. In our study we reported that the 52,3% of patients with CRC were over 70 and out of screen time, while only 47,7% were under 70. Early detection seems to be related to early stage of CRC and to an improved overall survival. Conclusion: The importance of early detection in colorectal cancers represents the most important outcome for OS. The risk of colorectal cancer is increased in elderly. Actual screening programmes cover less than 50% of population with colorectal cancer. Screening should be considered for patients over 70, due to the high number of new diagnosis in symptomatic disease and worst prognosis, in accordance with advanced cancer stage and comorbidities in elderly.